Foam-mat dried japanese threadfin bream (Nemipterus japonicus) powder with methyl cellulose as the foaming agent: Physicochemical and functional properties - Mohamed, Abdulrahim Abubakar; Mohammad Rashedi, Ismail Fitry; Rozzamri, Ashari; Bakar, Jamilah (Universiti Putra Malaysia, 2023)
Minced meat of Japanese threadfin bream (Nemipterus japonicus) was foam-mat dried at 70 and 80°C using methyl cellulose (MC) as the foaming agent at concentrations of 0.0, 0.5, 1.0, and 1.5% w/w. The objective was to determine the effect of drying temperature and amount of foaming agent incorporated on the physicochemical and functional properties of the powdered samples. Fish powders had a water activity (aw) of < 0.40, which significantly increased (p < 0.05) with increasing MC concentrations and drying temperatures. Protein solubility (PS) and water holding capacity (WHC) were inversely correlated with the drying temperature (r = -0.943 and -0.749, respectively). Emulsification property had a strong inverse correlation with MC (r = -0.839) as compared to temperature (r = 0.462). The TBARS and FFA values of the fish powders dried at 70°C were significantly lower than at 80°C (p < 0.05). No significant differences were obtained in their fat and ash contents, except for crude protein, which was significantly higher in the fish powder dried at 70°C. Drying at 70°C resulted in overall superior powder properties, with 0.5% MC being the best treatment.